The Endocrine Giants of Chronic Kidney Disease - Sourabh Sharma; Neha Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
Chronic Kidney Disease (CKD) is increasingly being recognized as an endo-metabolic disorder in which a cascade of hormonal and electrolyte imbalances impacts the morbidity and mortality. We propose six “endocrine giants” of CKD- anaemia, secondary hyperparathyroidism, hypovitaminosis D, hypogonadism, hyperkalaemia, and hyponatraemia- each exerting a detrimental effect on cardiovascular, skeletal, metabolic, and neurological health. Their early recognition and prompt management can attenuate downstream cardiometabolic sequelae. This “endocrine giants” framework provides an integrative approach to managing CKD as a multisystem endocrine disorder and offers practical direction for holistic nephrology care. Keywords: Chronic kidney disease, Anaemia, Secondary hyperparathyroidism, Hypovitaminosis D, Hyperkalaemia, Hyponatraemia, Hypogonadism